2017
DOI: 10.1038/s41598-017-16296-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of splicing mutations in disorders of sex development

Abstract: The presence of splicing sequence variants in genes responsible for sex development in humans may compromise correct biosynthesis of proteins involved in the normal development of gonads and external genitalia. In a cohort of Brazilian patients, we identified mutations in HSD17B3 and SRD5A2 which are both required for human sexual differentiation. A number of these mutations occurred within regions potentially critical for splicing regulation. Minigenes were used to validate the functional effect of mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Sixty-eight articles reported one or more patients with HSD17B3 mutations ( Supplemental Table S1 ) [ 1 , 3 , 4 , 5 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-eight articles reported one or more patients with HSD17B3 mutations ( Supplemental Table S1 ) [ 1 , 3 , 4 , 5 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent microRNA binding to the target region may lead to translational repression or degradation of the target region and gene silencing, for which it is hypothesized that the C allele of rs9332975 in the 3'-UTR region may have a higher affinity for microRNA, leading to a downregulation of SRD5A2 gene expression. Additionally, Calais et al [ 37 ] suggested that the c.544 G > A mutation in the SRD5A2 gene may potentially disrupt the binding of U1snRNP to the 5 'splice site, thereby inhibiting splicing initiation and consequently SRD5A2 gene expression. Furthermore, it has also been observed [ 28 ] that mutations in certain sites of SRD5A2 can affect its 5α-reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods have been used extensively in the characterization of splicing variants over the years, testing splicing disruption from a variety of variant types (intronic, missense, synonymous) across many different genomic contexts ( Gaildrat et al, 2010 ; Sharma et al, 2014 ; de Calais et al, 2017 ; Dionnet et al, 2020 ; Wai et al, 2020 ). While successful in research laboratories, their widespread use in clinical diagnostics is hindered by their relatively low throughput nature, since minigenes and RT-PCR primers must generally be tailored to each variant to be tested.…”
Section: Classification Of Potentially Splice Disrupting Variantsmentioning
confidence: 99%